Enhancing Dimensional Stability of Sengon Wood through Synergistic Citric Acid-Glycerol Cross-Linking and SiO2/TiO2 Nanocomposite Impregnation - Sartika; Istie Sekartining Rahayu; Wayan Darmawan; Andi Detti Yunianti; Esti Prihatini; Gilang Dwi Laksono; Rohmat Ismail (Department of Forestry, Faculty of Agriculture, University of Lampung, 2026)
Sengon wood (Falcataria moluccana) is a fast-growing, low-quality species. In this research, nanoparticle-based impregnation was used to improve the quality and characteristics of sengon wood. SiO2 nanoparticles derived from bamboo leaves were synthesized using the sol-gel method, while TiO2 nanoparticles and SiO2/TiO2 nanocomposites were synthesized using the hydrothermal method. A mixture of citric acid, glycerol, and nanoparticles (SiO2, TiO2, and SiO2/TiO2 composite) was formulated as an impregnation solution at 1% concentration. Sengon wood impregnation was conducted using a vacuum-pressure method. The physical properties tested included weight percent gain (WPG), bulking effect (BE), anti-swelling efficiency (ASE), water uptake (WU), and density. The size of the synthesized nanoparticles was analyzed using a particle size analyzer (PSA). The impregnated sengon wood was characterized using Fourier transform infrared spectroscopy (FTIR) to identify functional groups and X-ray diffraction (XRD) to determine the degree of crystallinity. PSA analysis showed that the material used in the impregnation process is nanoscale (< 100 nm) and exhibits the best dispersion stability in the SiO2/TiO2 nanocomposite. Nanoparticle-impregnated sengon wood exhibited reduced WU and improved dimensional stability compared to untreated samples, especially in citric acid-glycerol and composite nanoparticle treatments. FTIR analysis identified the formation of ester bonds and the reduction of hydroxyl groups, and XRD analysis showed a decrease in crystallinity upon impregnation with nanoparticles and a citric acid-glycerol mixture. Overall, the use of citric acid-glycerol with the nanocomposite showed effectiveness in improving the dimensional stability and physical properties of sengon wood. Keywords: citric acid-glycerol, dimensional stability, sengon, SiO2/TiO2 nanocomposite, wood modification